MENINGKATKAN KEMAMPUAN GURU PENDIDIKAN AGAMA ISLAM DALAM MELAKSANAKAN PENELITIAN TINDAKAN KELAS MELALUI KEGIATAN PEMBINAAN DAN PEMBIMBINGAN - Yanti Budayasti (Balai Diklat Keagamaan Bandung, 2023)
The research is motivated by the limited capacity of Islamic religious education (PAI) instructors in the Ministry of Religion of Cianjur Regency to conduct Classroom Action Research. Therefore, the researcher attempts to enhance the skills of the teachers of the district. This study employs a qualitative research methodology with action research methods along with mentoring techniques. The data collected are using a variety of methods, such as observation techniques, interviews, and portfolios. Based on the findings and analysis, the Islamic religious education teachers’ ability in conducting action research increased. This is demonstrated by the following. 1) The percentage of PAI teachers engaged in CAR activities which was initially 55%, has improved to 88% after the last cycle. It requires that coaching and mentoring activities for Islamic Religion education teachers have a positive effect on the teacher's ability to carry out PTK.